Linear and multivalent PEGylation of the tobacco mosaic virus and the effects on its biological properties - Caballero, Reca Marian; González-Gamboa, Ivonne; Craig, Stephen L.; Steinmetz, Nicole F. (Frontiers in Virology, 2023)
Plant virus-based nanoparticles (VNPs) offer a bio-inspired approach to the delivery of drugs and imaging agents. The chemical addressability, biocompatibility, and scalable manufacturability make VNPs a promising alternative to synthetic delivery platforms. However, proteinaceous VNPs and synthetic nanoparticles (NPs) alike are readily recognized and cleared by the immune system and mechanisms such as opsonization and phagocytosis. Shielding strategies such as PEGylation are commonly used to mitigate premature NP clearance. Here, we investigated polyethylene glycol (PEG) coatings on tobacco mosaic virus (TMV), which was used as a model nanocarrier system. Specifically, we evaluated the effects of linear and multivalent PEG coatings at varying chain lengths on serum protein adsorption, antibody recognition, and macrophage uptake. Linear and multivalent PEGs of MW 2000 and 5000 Da were successfully grafted onto TMV at ~20-40% conjugation efficiencies, and the degree of crosslinking as a function of PEG arm valency and length was outlined. PEGylation resulted in the modulation of TMV-macrophage interactions and reduced corona formation as well as antibody recognition. Linear and multivalent PEG 5000 formulations (but not PEG 2000) reduced α-TMV antibody recognition, while shorter, multivalent PEG coatings significantly reduced α-PEG recognition – this highlights an interesting interplay between the NP and PEG itself in potential antigenicity and should be an important consideration in PEGylation strategies. This work provides insight in PEGylation strategies of VNPs which may improve their possibility of implementation in clinical applications.